Moderate energy restriction with high protein diet results in healthier outcome in women - Puurtinen Risto; Hulmi Juha J; Matintupa Olle; Huovinen Heikki; Mero Antti A; Hohtari Hannele; Karila Tuomo AM (Taylor & Francis Group, 2010)
Abstract Background The present study compares two different weight reduction regimens both with a moderately high protein intake on body composition, serum hormone concentration and strength performance in non-competitive female athletes. Methods Fifteen normal weighted women involved in recreational resistance training and aerobic training were recruited for the study (age 28.5 ± 6.3 yr, height 167.0 ± 7.0 cm, body mass 66.3 ± 4.2 kg, body mass index 23.8 ± 1.8, mean ± SD). They were randomized into two groups. The 1 KG group (n = 8; energy deficit 1100 kcal/day) was supervised to reduce body weight by 1 kg per week and the 0.5 KG group (n = 7; energy deficit 550 kcal/day) by 0.5 kg per week, respectively. In both groups protein intake was kept at least 1.4 g/kg body weight/day and the weight reduction lasted four weeks. At the beginning of the study the energy need was calculated using food and training diaries. The same measurements were done before and after the 4-week weight reduction period including total body composition (DXA), serum hormone concentrations, jumping ability and strength measurements Results During the 4-week weight reduction period there were no changes in lean body mass and bone mass, but total body mass, fat mass and fat percentage decreased significantly in both groups. The changes were greater in the 1 KG group than in the 0.5 KG group in total body mass (p < 0.001), fat mass (p < 0.001) and fat percentage (p < 0.01). Serum testosterone concentration decreased significantly from 1.8 ± 1.0 to 1.4 ± 0.9 nmol/l (p < 0.01) in 1 KG and the change was greater in 1 KG (30%, p < 0.001) than in 0.5 KG (3%). On the other hand, SHBG increased significantly in 1 KG from 63.4 ± 17.7 to 82.4 ± 33.0 nmol/l (p < 0.05) during the weight reducing regimen. After the 4-week period there were no changes in strength performance in 0.5 KG group, however in 1 KG maximal strength in bench press decreased (p < 0.05) while endurance strength in squat and counter movement jump improved (p < 0.05) Conclusion It is concluded that a weight reduction by 0.5 kg per week with ~1.4 g protein/kg body weight/day can be recommended to normal weighted, physically active women instead of a larger (e.g. 1 kg per week) weight reduction because the latter may lead to a catabolic state. Vertical jumping performance is improved when fat mass and body weight decrease. Thus a moderate weight reduction prior to a major event could be considered beneficial for normal built athletes in jumping events.